Mechanisms of gut microbiota in host fat deposition: metabolites, signaling pathways, and translational applications - Liu, Sha (Frontiers in Microbiology, 2025)
Obesity and metabolic diseases are global health challenges, with gut microbiota playing a critical role in host fat deposition through symbiotic interactions. In recent years, the gut microbiota, as an important factor regulating fat deposition, has received widespread attention. Numerous studies have confirmed that gut microbes influence host fat accumulation by regulating energy metabolism, inflammatory response, and gut barrier function. In this review, we summarized the key roles of gut microbial metabolites, including short-chain fatty acids (SCFAs), bile acids, tryptophan metabolites, lipopolysaccharides (LPS), branched-chain amino acids (BCAAs), and trimethylamine N-oxide (TMAO) in host epigenetic regulation and lipid metabolism, and explored their regulatory mechanisms through mediated signaling pathways, including Wnt/β-catenin signaling pathway, transforming growth factor beta/SMAD3 pathway (TGF-β/SMAD3), peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT/enhancer-binding protein alpha (C/EBPα), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). In terms of translational applications, we described the research progress and application potentials of intervention strategies, such as probiotics, prebiotics, synbiotics, postbiotics, and fecal transplantation in obesity control and animal production. Finally, we proposed the current bottlenecks and translational challenges in obesity control by precision nutrition and microecological intervention, and look forward to future directions. This review provides a theoretical basis for the in-depth understanding of the interactions between gut microbiota and host metabolism, and serves as a reference for the prevention and control of metabolic diseases by developing nutritional intervention strategies for animals.